2017
DOI: 10.1007/s10856-017-5848-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of negatively and positively charged Ti metal surfaces on ceramic coating adhesion and cell response

Abstract: This manuscript reports an evaluation of the effects of simple chemical-heat treatments on the deposition of different ceramic coatings, i.e., TiO, CaTiO and CaP, on commercially pure titanium (cp-Ti) and Ti6Al4V and the influence of the coatings on cells interaction with the surfaces. The ceramic materials were prepared by the sol-gel method and the coating adhesion was analyzed by pull-off bending tests. The wettability of positively or negatively charged surfaces was characterized by contact angle measureme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…To build effective tissues, cells need to first develop a suitable morphology and physical features, such as filopodia, in the in vitro conditions [3]. Cells reorganize by interactions with material properties, such as topography [4], mechanical strength [5], and surface potential [6,7,8]. Moreover, they adjust the shape and morphology to a surface geometry, thus, the design of the scaffold is crucial in controlling cells behavior, development, and proliferation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…To build effective tissues, cells need to first develop a suitable morphology and physical features, such as filopodia, in the in vitro conditions [3]. Cells reorganize by interactions with material properties, such as topography [4], mechanical strength [5], and surface potential [6,7,8]. Moreover, they adjust the shape and morphology to a surface geometry, thus, the design of the scaffold is crucial in controlling cells behavior, development, and proliferation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These surface-bound host factors may also serve as specific receptors for both tissue cells and colonizing bacteria. Titanium, for instance, has a positively charged surface and will initially form non-covalent bonds with negatively charged proteins such as albumin and fibronectin ( Jager et al., 2017 , Do Nascimento et al., 2017 ). Fibronectin has been observed to promote bacterial adhesion, whereas albumin and whole serum appear to inhibit bacterial adhesion to biomaterial surfaces ( Ribeiro et al., 2012 ).…”
Section: Titanium As An Orthopedic Biomaterialsmentioning
confidence: 99%
“…Primary cultures can provide information more relevant to clinical outcomes when compared to immortalized cell lines such as Saos-2 or MG63, and are also increasingly used in the biomaterials field with tissue engineering applications, and for these reasons were chosen for this study. 30 Although several reports exist on stem cell/osteoblast biocompatibility of either titanium [31][32][33][34][35] or PU, [36][37][38][39] no studies were found on PU/Ti composites. Therefore, the potential cytotoxicity of those used in this study was assessed with both HDPSC and osteoblasts.…”
Section: Biocompatibility Of Compositesmentioning
confidence: 99%
“…This is in contrast with previous reports where either HDPSC or osteoblast were cultured, in the absence of a polymer, on laser sintered or acid etched titanium alloys and where it was observed no difference in cell adhesion. 31 Surface roughness, 32 surface chemistry, 33,34 zeta potential, and surface energy 22,30 have been proposed as the main factors contributing to osteoblast attachment to titanium implants, but to our knowledge, there is no similar study on HDPSC. 35 Although it has been reported that committed cells (human osteoblasts) display better proliferation, distribution, and adhesion in 2D cultures on roughened titanium surface compared to HDPSC, 40 it is possible that HDPSC exhibited higher proliferation at shorter times either due to the higher proliferative index as many multipotent cells or due to the stimulating effect of titanium.…”
Section: Biocompatibility Of Compositesmentioning
confidence: 99%